ERRORS IN USING DICTION AND GRAMMAR OF STUDENTS’ FINAL COURSE ACADEMIC WRITING OF DEPARTMENT OF ENGLISH EDUCATION AT JAKARTA STATE UNIVERSITY - Jabal Nur (ELTIES : English Language Teaching for EFL Learners, 2019)
This research aims to analyze in depth the use of diction error, subject and predicate, and the cause of the error on students of English Education in State University of Jakarta. The research is a qualitative study using descriptive methods. The Instrument of this research is 50 students of third semester essay at the end of the task of writing an academic course of the academic year 2012/2013. The results of this research showed the majority of student errors occurred in the category of diction. Diction ranks first in the percentage of error as much as 63%, followed by subject and verb agreement 37%, and the cause of the error is due to the influence of the first language, translation, and carelessness